2011
DOI: 10.1007/s10142-011-0258-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of barley malting quality QTLs with Ds transposons

Abstract: Various functional genomic tools are being used to identify and characterize genes in plants. The Activator/Dissociation (Ac/Ds) transposon-based approach offers great potential, especially in barley, due to its limited success of genetic transformation and its large genome size. The bias of the Ac/Ds system towards genic regions and its tendency toward localized transpositions can greatly enhance the discovery and tagging of genes linked to Ds. Barley is a key ingredient in malting and brewing industry; there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Genomic DNA was extracted using a modified phenol/chloroform method as described by Singh et al. . DNA quality and quantity was analysed using a Nanodrop spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted using a modified phenol/chloroform method as described by Singh et al. . DNA quality and quantity was analysed using a Nanodrop spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to seeding, seeds of wild barley genotypes were vernalized at 4°C for 4 weeks. Genomic DNA was extracted using a modified phenol/chloroform method as described by Singh et al 2012. DNA quality and quantity was analysed using a Nanodrop spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Ds remobilisation has been obtained by two approaches, namely, by conventional crossing of the original Ds-carrying line with an AcTPase-expressing parent and by genetic transformation of the Ds-carrying line with a construct carrying the AcTPase gene. The latter approach unexpectedly showed a higher remobilisation rate, perhaps due to the alteration of the chromatin methylation pattern occurring during the in vitro cultivation phase (Singh et al 2012). Interestingly, Singh et al (2006) reported a very high insertion rate (86 %) in genic regions as observed in maize and rice, while Zhao et al (2006) observed some tendency for Ds elements to target low-copy, matrix-attachment regions.…”
Section: Insertional Mutagenesismentioning
confidence: 99%
“…This mutant has been useful for elucidating the control of cleistogamous flowering (Anwar et al, 2018). Other tagged barley lines have played a role in investigating the genes associated with root growth and malting quality (Kaur et al, 2013; Singh et al, 2012; Singh and Singh, 2017).…”
Section: Genbank Accession Numbers Of Dst Sequences Flanking Ds‐bar Imentioning
confidence: 99%